Systematic Investigation of Gettering Effects on 4th Row Element Impurities in Si by Dopant Atoms - Koji Sueoka; Ken Kamimura; Seiji Shiba (Advances in Materials Science and Engineering, 2009)
The gettering of 4th row element impurities (K, Ca, 3d transition metals, and Zn) in Si crystals by dopant atoms was systematically investigated by first-principles calculation through evaluation of the diffusion barrier and the binding energy. The dopant atoms considered include p-type dopants (B), n-type dopants (P, As, Sb), or light elements (C, O). It was found that (1) the diffusion barrier of impurity atoms decreases with an increase in their atomic number up to Ni, (2) B atom becomes an efficient gettering center for metals except for Ni, (3) most of the metals except for Fe and Co cannot be gettered by n-type dopants, and (4) C and O atoms alone do not become efficient gettering centers for the metals used in actual LSI processes. The vacancy 𝑉𝑐 and n-type dopant complexes (P𝑉𝑐, As𝑉𝑐, Sb𝑉𝑐) can be efficient gettering centers for Cu in n/n+ epitaxial wafers.